I Infrastructure development: Improving on execution systems - Edoghogho Ogbeifun; Charles Mbohwa; Jan-Harm C Pretorius (Journal of Construction Project Management and Innovation)
The use of the traditional procurement system for the execution of capital construction projects has been subjected to different levels of criticism. Despite this it is still the method most commonly used for the execution of capital development projects in the public and private sectors in many developing countries. Some of the most prominent criticisms include cost and time overruns, the inability to fast-track the completion of capital projects, huge human capacity in the client and project execution teams and the process being exposed to different levels of dispute adjudication. Nevertheless, these shortcomings can be ameliorated through the pragmatic use of the concept of phased development and the fragmentation of mega projects into smaller lots for ease of execution. This concept encourages the use of multiple project execution teams, facilitates the simultaneous execution of the different lots and creates an internal drive for healthy competition among project execution teams. This would result in the effective delivery of mega projects with the possibility of time and cost savings. The exploratory method of qualitative research was adopted in the study of a mega project, which was fragmented into smaller lots and executed in a higher education institution in Nigeria. The findings reveal that the mega project was executed within the time schedule and with a significant cost saving. Therefore, making contextual improvements in the traditional procurement system and mode of executing mega projects can enhance effective project delivery devoid of the setbacks associated with the traditional procurement system.